Answer:
[tex]\huge\boxed{x=27}[/tex]
Step-by-step explanation:
[tex]\dfrac{x}{3}-3=\dfrac{x}{9}+3\qquad\text{add 3 to both sides}\\\\\dfrac{x}{3}-3+3=\dfrac{x}{9}+3+3\\\\\dfrac{x}{3}=\dfrac{x}{9}+6\qquad\text{subtaract}\ \dfrac{x}{9}\ \text{from both sides}\\\\\dfrac{x}{3}-\dfrac{x}{9}=\dfrac{x}{9}-\dfrac{x}{9}+6\\\\\dfrac{(x)(3)}{(3)(3)}-\dfrac{x}{9}=6\\\\\dfrac{3x}{9}-\dfrac{x}{9}=6\\\\\dfrac{2x}{9}=6\qquad\text{multiply both sides by 9}\\\\9\!\!\!\!\diagup\cdot\dfrac{2x}{9\!\!\!\!\diagup}=(9)(6)\\\\2x=54\qquad\text{divide both sides by 2}\\\\\dfrac{2x}{2}=\dfrac{54}{2}[/tex]
[tex]x=27[/tex]